PENGARUH STRATEGI PEMASARAN ONLINE UNTUK MENINGKATKAN DAYA SAING UMKM(STUDI KASUS KOPI KENANGAN JAKARTA TIMUR) - Lovenda Natanael; Phebe Trivena Panjaitan, Shafi Shabira, Siti Arum, Indhah Kresnawati Rahayu, Natasya Dwi Kencana Ang (Prosiding Seminar Nasional Indonesia, 2024)
This study aimed to analyze the influence of digital marketing strategies and traditional marketing strategies on enhancing competitiveness. The sample consisted of 100 individuals, with data collected through questionnaire distribution. A quantitative methodology was employed, utilizing primary data. The analysis was conducted using multiple linear regression after satisfying tests for validity, reliability, and classical assumptions. The collected data was inputted into SPSS V.29 software. The research findings revealed that partially, digital marketing strategies exerted a positive and significant impact on the competitiveness of small and medium enterprises (SMEs). Similarly, marketing strategies also had a positive and significant effect on SME competitiveness. Simultaneously, both digital marketing strategy and marketing strategy demonstrated a positive and significant influence on SME competitiveness. The coefficient of determination indicated that 75.3% of the variance in competitiveness could be explained by digital marketing strategy and marketing strategy, while the remainder was influenced by other variables not accounted for in this research. These results align with previous studies emphasizing the importance of implementing effective digital marketing strategies and appropriate marketing strategies to improve SME competitive positioning in the current digital era. The managerial implication suggests that companies need to integrate digital marketing strategies and marketing strategies cohesively to enhance their competitive advantage.